A Dual‐Ion Battery Constructed with Aluminum Foil Anode and Mesocarbon Microbead Cathode via an Alloying/Intercalation Process in an Ionic Liquid Electrolyte. Issue 23 (25th August 2016) - Zhang, Fan; Ji, Bifa; Tong, Xuefeng; Sheng, Maohua; Zhang, Xiaolong; Lee, Chun‐Sing; Tang, Yongbing
Abstract : A novel dual‐ion battery constructed with aluminum foil anode and mesocarbon microbead (MCMB) cathode based on a lithium‐salt containing ionic liquid electrolyte is prepared. The working mechanism of this Al‐MCMB dual‐ion battery is demonstrated to be intercalation/deintercalation of anions into/from the MCMB cathode and AlLi alloying/dealloying at the Al anode. Owing to the good stability of ionic liquid at high working voltage and the protection of fluoroethylene carbonate additive in the electrolyte by forming stable solid electrolyte interphase film on the Al foil, the battery presents superior cycling stability at high cut‐off voltage of 4.8 V with a reversible capacity of 98 mAh g −1 after 300 cycles at 0.5 C with negligible decay. Moreover, as the Al foil is directly utilized as both anode material and current collector, the energy density of the packaged Al‐MCMB cell can be further increased, which is estimated to be 221 W h kg −1 at the power density of 109 W kg −1 and remains 185 W h kg −1 at 1141 W kg −1, much better than most commercial lithium‐ion batteries. Abstract : A novel dual‐ion battery constructed with aluminum foil anode and mesocarbon microbead cathode is designed in this work based on an ionic liquid electrolyte. The battery shows only 2% decrease after 300 cycles. Moreover, the energy density of the packaged battery can be estimated to be 221 W h kg −1 at the power density of 109 W kg −1, much higher than most commercial lithium‐ion batteries.